Effect of administering dexmedetomidine with or without atropine on cardiac troponin I level in isoflurane-anesthetized dogs - HUANG, Hsin-Yu; LIAO, Kai-Yueh; SHIA, Wei-Yau; CHANG, Chao-Chin; WANG, Hsien-Chi (Journal of Veterinary Medical Science, 2021)
We aimed to determine whether dexmedetomidine administration with or without atropine increases cardiac troponin I (cTnI) level in healthy dogs. We hypothesized that 10 µg/kg dexmedetomidine + atropine increases the cTnI level, whereas 5 µg/kg dexmedetomidine + atropine does not. Eighteen healthy, pet dogs that underwent an orthopedic surgery or ovariohysterectomy were included in this study. The dogs were randomly assigned to atropine (0.02 mg/kg)–dexmedetomidine (10 µg/kg), saline–dexmedetomidine (10 µg/kg), and atropine (0.02 mg/kg)–dexmedetomidine (5 µg/kg) groups. Each dog was premedicated with atropine or saline intramuscularly (IM). After 10 min, they were IM injected with dexmedetomidine (10 or 5 µg/kg)–morphine (0.5 mg/kg)–midazolam (0.2 mg/kg). Following this, anesthesia was induced after 10 min with propofol and maintained with isoflurane in 100% oxygen. The median plasma cTnI level at 6, 12 and 24 hr after premedication was significantly higher than that at baseline. The cTnI level in the atropine–dexmedetomidine (10 µg/kg) group was significantly higher than that in the saline–dexmedetomidine (10 µg/kg) and atropine–dexmedetomidine (5 µg/kg) groups at 6 and 12 hr after premedication. The cTnI level returned to normal within 72 hr after premedication in all groups. The administration of atropine in combination with 10 µg/kg dexmedetomidine increased the cTnI level, indicating subclinical myocardial damage.